English Language textbooks and portrayal of culture: A content analysis - Abd Rashid, Ruzai Syarilili Aiyu; Engku Ibrahim, Engku Haliza (EDP Sciences, 2018)
Research has shown that there is a need to use materials that are cultural sensitive and context-appropriate in the EFL classroom. It is imperative that teaching materials match with the goals, objectives and philosophy of the programme. This is to ensure that the materials are congruent with the learners’ attitudes, religious beliefs and preferences. Thus, this study aims to find out if there were materials that are not in harmony with Islam. The sampling of this study was taken from 5 textbooks that were being used in an intensive English course. The findings from this study showed that in general the contents of the ELT textbooks could be categorised into three categories of neutral, positive and negative. Additionally, it was also discovered that these themes fall under community knowledge, beliefs and values of the western culture in Byram’s (1993) cultural content checklist. This study has strong implications for the use of ready-made textbooks in the EFL context.